Factors affecting the price level of award-winning securities in the sustainable excellence group of the stock exchange of Thailand - Jankanakittikul, Thanomsilp; Watchalaanun, Tanawat; Nonthapot, Sakkarin (Asian Economic and Financial Review, 2025)
The purpose of this study is to examine the financial ratio factors and the impact of the awards in the Sustainability Excellence group at each level, which affect the price level of securities awarded in the Sustainability Excellence group on the Stock Exchange of Thailand. The study employed time series data from 32 companies from Quarter 1 of 2021 to Quarter 1 of 2024. The analysis utilized the panel unit root with the CIPS test. We used the Panel Autoregressive Distributed Lag (Panel ARDL) model and the Pool Mean Group (PMG) method to determine how financial ratios affected the prices of securities. The Fixed Effect (FE) and Random Effect (RE) models were used to analyze how rewards affected the prices of securities. The results of the study show that (1) the variable factors in financial ratios impact both short-term and long-term equilibrium. (2) The RE model yielded appropriate results. We found that the awarding of a Sustainability Award of Honor significantly and positively impacted the price of securities. Therefore, executives should prioritize the utilization of the company's assets with the aim of continuous sustainability.